Factors that determines individual investment alternatives / Mohd Azrin Basirum - Basirum, Mohd Azrin (Faculty of Business and Management, 2010)
The study was conducted to find out the significant relationship between independent variables with dependent variable. The variables selected are investment choice, investment return, personal income, and individual knowledge. The dependent variable is individual investment alternative. The method used for this study is the regression analysis. The result then has been interpreted base on the correlation, coefficient correlation, F-statistic and T statistic. The data used for the study are collected for the period of June until August year of 2010. Base on the result, it was concluded that investment choice is not significant to the individual investment alternative. However, there are significant relationship between investment return, personal income and individual knowledge to the investment alternative.